A New Coding Paradigm for the Primitive Relay Channel - Mondelli, Marco; Hassani, S. Hamed; Urbanke, Rudiger (2018 IEEE International Symposium on Information Theory (ISIT), 2018)
We present a coding paradigm that provides a new achievable rate for the primitive relay channel by combining compress-and-forward and decode-and-forward with a chaining construction. In the primitive relay channel model, the source broadcasts a message to the relay and to the destination; and the relay facilitates this communication by sending an additional message to the destination through a separate channel. Two well-known coding approaches for this setting are decode-and-forward and compress-and-forward: in the former, the relay decodes the message and sends some of the information to the destination; in the latter, the relay does not attempt to decode, but it sends a compressed description of the received sequence to the destination via Wyner-Ziv coding. In our scheme, we transmit over pairs of blocks and we use compress-and-forward for the first block and decode-and-forward for the second. In particular, in the first block, the relay does not attempt to decode and it sends only a part of the compressed description of the received sequence; in the second block, the relay decodes the message and sends this information plus the remaining part of the compressed sequence relative to the first block. As a result, we strictly outperform both compress-and- forward and decode-and-forward. Furthermore, this paradigm can be implemented with a low-complexity polar coding scheme that has the typical attractive features of polar codes, i.e., quasi-linear encoding/decoding complexity and super-polynomial decay of the error probability. Throughout the paper we consider as a running example the special case of the erasure relay channel and we compare the rates achievable by our proposed scheme with the existing upper and lower bounds.